Reflection on researching EFL reading in academic context - Radzuwan, Ab Rashid; Hamzeh Jamal, Aleshoush (2019)
For many years a great deal of research on reading strategies has mainly focused on the cognitive and linguistic aspects. The main criticism against these two aspects of language learning is that they overlooked the social context of learning to a great extent. The cognitive and the linguistic frameworks are not comprehensive enough in understanding the process of reading especially among the EFL learners. This paper starts with some backgrounds on academic reading experiences of EFL learners, and researching reading within the sociocultural context. Then it discusses some the challenges of methodological and ethical issues in employing a qualitative to research in the area of reading. This paper covers issues related to two qualitative methods of data collection, reading diary and interview. It concludes that the challenging methodological issues in researching academic reading comprehension require cautious consideration throughout the research process. It recommends that new ethics guidelines be developed by ethics board members for the reference of researchers who embark on research in this area.